2023
DOI: 10.1186/s40168-023-01605-y
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum enables blood urate control in mice through degradation of nucleosides in gastrointestinal tract

Abstract: Background Lactobacillus species in gut microbiota shows great promise in alleviation of metabolic diseases. However, little is known about the molecular mechanism of how Lactobacillus interacts with metabolites in circulation. Here, using high nucleoside intake to induce hyperuricemia in mice, we investigated the improvement in systemic urate metabolism by oral administration of L. plantarum via different host pathways. Results Gene expression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Heterogeneous expression in E. coli and gene knockout in LGG demonstrated that these genes play different roles in nucleoside degradation. Similar to these findings, degradation function genes were also reported in Lactiplantibacillus plantarum , which catalyzed the hydrolysis of nucleosides into nucleobases in mice 21 . A recent study also showed that Clostridium sporogenes from human subjects has the pbuX gene for the conversion of UA to SCFAs 47 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Heterogeneous expression in E. coli and gene knockout in LGG demonstrated that these genes play different roles in nucleoside degradation. Similar to these findings, degradation function genes were also reported in Lactiplantibacillus plantarum , which catalyzed the hydrolysis of nucleosides into nucleobases in mice 21 . A recent study also showed that Clostridium sporogenes from human subjects has the pbuX gene for the conversion of UA to SCFAs 47 .…”
Section: Discussionsupporting
confidence: 81%
“…Recent research has demonstrated that some gut microbes participate in the mechanism of UA degradation. For example, the oral administration of Limosilactobacillus fermentum and Lactiplantibacillus plantarum isolated from fermented food has been shown to strongly degrade UA in mice 21 , 22 . Lactobacillus gasseri PA3 can decrease the UA concentration and increase the relative abundance of Lactobacillus 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by He et al [17], inulin-type prebiotics were found to lower serum UA levels in patients with end-stage renal disease by increasing the degradation of UA in the intestinal microbiota. Studies have revealed that the ribonucleoside hydrolase in Lactobacillus can hydrolyze nucleosides into nucleobases in order to reduce the serum UA level in mice via the degrading of purine nucleosides and reducing purine absorption in the intestine [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections of 5–8 mm were prepared from the paraffin-embedded tissue. Xylene ethanol dewaxed and hydrated the paraffin sections, and the dewaxed sections were stained with hematoxylin-eosin (H&E) solution ( 8 ).…”
Section: Methodsmentioning
confidence: 99%